Natural cork agglomerate enabled mechanically robust rigid polyurethane foams with outstanding viscoelastic damping properties. (5th March 2021) - Park, Sung Jun; Cho, Seung-Hyun; Seo, Hee Won; Nam, Jae-Do; Suhr, Jonghwan
Abstract: This study investigates the mechanical and damping properties of natural cork particle reinforced rigid polyurethane (PU) composite foams, and also the structure-properties relationship between their cellular microstructural morphology and their thermomechanical properties. The linear relation between reaction rate, cell size, and free rise density (FRD) of Cork/PU composite with respect to the cork loading fraction was experimentally observed and analytically confirmed. It was found that the cork particles could effectively tailor the static and dynamic viscoelastic properties of composite foams. Importantly, it was observed in the dynamic viscoelastic characterization that the Cork/PU composite foams exhibited the increase in both storage and loss moduli, which is typically compromised for each other. These results could provide broad insight and guidance in developing a novel polymeric foam with mechanical robustness and energy absorbing capability for various structural applications including electrical vehicle and drone, which requires both lightweight and strength/stiffness. Graphical abstract: Image 1 Highlights: Effects of cork particle on structure-properties relationship of polyurethane foam. Mechanical behavior of cork particle filled polyurethane foam. Increasing of hard segment due to reaction between cork particle and isocyanate. Improvement of both storage and loss modulus.